2023
DOI: 10.3389/fimmu.2023.1195858
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of JAK inhibitors on effect and safety in alopecia areata: a systematic review and meta-analysis of 2018 patients

Abstract: BackgroundJAK inhibitors treat various autoimmune diseases, but an updated systematic review in treating alopecia areata is currently lacking.ObjectiveEvaluate the specific efficacy and safety of JAK inhibitors in alopecia areata by systematic review and meta-analysis.MethodsEligible studies in PubMed, Embase, Web of Science, and Clinical Trials up to May 30, 2022, were searched. We enrolled in randomized controlled trials and observational studies of applying JAK inhibitors in alopecia areata.Results6 randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Furthermore, based on our clinical experience, we found that females and elders were more vulnerable to the adverse effects of corticosteroids. The patient in our case refused glucocorticoid therapy because of obesity and menstrual disorders that might be caused by the inability to receive glucocorticoid therapy; (3) several reviews on the overall safety of JAK inhibitors have been published recently, suggesting that JAKi has good security with a low risk of venous thromboembolism, cardiac events, and cancer ( 13 17 ). As such, follow-up according to guidelines greatly ensured patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, based on our clinical experience, we found that females and elders were more vulnerable to the adverse effects of corticosteroids. The patient in our case refused glucocorticoid therapy because of obesity and menstrual disorders that might be caused by the inability to receive glucocorticoid therapy; (3) several reviews on the overall safety of JAK inhibitors have been published recently, suggesting that JAKi has good security with a low risk of venous thromboembolism, cardiac events, and cancer ( 13 17 ). As such, follow-up according to guidelines greatly ensured patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…Other JAK inhibitors were used off‐label in alopecia areata, including tofacitinib (JAK 1/3 inhibitor) at a dose of 2 × 5 mg/day, ruxolitinib (JAK 1/2 inhibitor) at a dose of 2 × 20 mg/day, upadacitinib (JAK 1 inhibitor) at a dose of 30 mg/day as well as delgocitinib (JAK 1‐3/TYK2) in Japan at a dose of 30 mg/day. Brepocitinib at a dose of 30–60 mg/day (TYK2/JAK1 inhibitor), deuruxolitinib at a dose of 2 × 8 mg/day are at various pre‐approval stages of drug development for alopecia areata 38,39 …”
Section: Therapeutic Managementmentioning
confidence: 99%